2009
DOI: 10.1016/j.ajhg.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SPINT2 Cause a Syndromic Form of Congenital Sodium Diarrhea

Abstract: Autosomal-recessive congenital sodium diarrhea (CSD) is characterized by perinatal onset of a persistent watery diarrhea with nonproportionally high fecal sodium excretion. Defective jejunal brush-border Na(+)/H(+) exchange has been reported in three sporadic patients, but the molecular basis of the disease has not been elucidated. We reviewed data from a large cohort of CSD patients (n = 24) and distinguished CSD associated with choanal or anal atresia, hypertelorism, and corneal erosions--i.e., a syndromic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
123
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 29 publications
3
123
0
4
Order By: Relevance
“…Notably, a recent study revealed that mutation of the SPINT2 gene results in a syndromic form of congenital sodium diarrhea, which also indicates a significant role for this membrane-bound serine protease inhibitor in the intestinal epithelial function. 32 The important role of HAI-1/SPINT1 in the colonic mucosa was also shown in a model for mucosal injury that involves DSS administration. In this model, DSS seems to be directly toxic to colonic epithelial cells of the basal crypts and affects the integrity of the mucosal barrier, and this mouse colitis model is widely used for the study of human IBD.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, a recent study revealed that mutation of the SPINT2 gene results in a syndromic form of congenital sodium diarrhea, which also indicates a significant role for this membrane-bound serine protease inhibitor in the intestinal epithelial function. 32 The important role of HAI-1/SPINT1 in the colonic mucosa was also shown in a model for mucosal injury that involves DSS administration. In this model, DSS seems to be directly toxic to colonic epithelial cells of the basal crypts and affects the integrity of the mucosal barrier, and this mouse colitis model is widely used for the study of human IBD.…”
Section: Discussionmentioning
confidence: 93%
“…Our proposal that HAI-2 is essential for matriptase expression in intestinal epithelium by preventing the "consumptive depletion" of matriptase may also explain the etiology of the sodium-selective diarrhea that is associated with congenital HAI-2 deficiency in humans (56). The epithelial sodium channel ENaC is critical for sodium reabsorption in the distal colon, and the activity of ENaC in the distal colon is dependent on its proteolytic activation by the matriptase-prostasin system (53).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, to date, the known complement of mutated SPINT2 alleles all either directed the production of HAI2 proteins at lower levels or with lower inhibitory activity (Heinz-Erian et al, 2009), whereas the phenotypic consequence of complete Spint2 deficiency has been analyzed only in mice. Also, as only SPINT2-deficient individuals that completed term development have been available for clinical evaluation, it is premature to discuss potential species-specific variations in the developmental manifestations of the loss of HAI2.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in postnatal epithelial function, such as persistent sodium diarrhea, corneal erosions and abnormal hair, are also associated with SPINT2 deficiency (Heinz-Erian et al, 2009). The SPINT2 gene encodes a serine protease inhibitor, hepatocyte growth factor activator inhibitor (HAI) 2 (also known as placental bikunin; hereafter HAI2) (Kawaguchi et al, 1997;Marlor et al, 1997), and reduced expression of HAI2 or synthesis of HAI2 variants with reduced in vitro inhibitory activity is common to all the mutated SPINT2 alleles (Heinz-Erian et al, 2009). This raises the possibility that key morphogenic processes, such as organ and digit specification and tubulogenesis, may require the fine-tuning of pericellular proteolytic activity through HAI2 silencing of unknown target proteases.…”
Section: Introductionmentioning
confidence: 99%